Images of Women in the Sermons of Guillaume Pepin (c.1465-1533) - Taylor, Larissa (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1994)
AbstractThe stereotype of the misogynistic medieval churchman persists in almost all scholarly assessments of gender attitudes and beliefs in the premodern period. Such sweeping generalizations do little to help us understand attitudes in one particular time and place, or changes over time; studies of individuals allow a more nuanced and richer understanding of male beliefs about women. Sermons in the late Middle Ages exhibit the full range of attitudes about women. In the sermons of Guillaume Pépin (c. 1465-1533), we find the preaching of a man who did not categorize women as the personification of Good or Evil, but talked at length about women and their problems in daily life with sympathy and compassion. The figures he evokes in his sermons are quite often strong, independent-minded women. Comparison with sermons in the mid-sixteenth century shows that many later preachers conform more closely to the stereotype, with the amount of attention given to women in sermons decreasing dramatically and negative descriptions predominating. Language is used much differently, and the resulting images of women are one-dimensional, with the female sex portrayed as subordinate, weak, and silly. These changes can be attributed to a number of factors, including the simplified sermon structure of the post Reformation period, the Reformation and misconceptions about the priesthood of all believers, the attempt to impose Catholic orthodoxy, and an increasing emphasis on the "natural order" of things.